Theoretical and Methodological Basis of the Use of Psychological Technological Methods by Investigators in the Process of Suspect and Accusation - Komilova Manzura Avazjon Qizi (Researchparks Publishing, 2022)
This article discusses the basic psychological and technical rules and procedures of the interrogation process, the importance of the investigation in criminal cases. The main methods of obtaining evidence are analyzed by interrogators and investigators.